Sonothrombolysis Improves Myocardial Dynamics and Microvascular Obstruction Preventing Left Ventricular Remodeling in Patients With ST Elevation Myocardial Infarction. (April 2020) - Aguiar, Miguel O.D.; Tavares, Bruno G.; Tsutsui, Jeane M.; Fava, Agostina M.; Borges, Bruno C.; Oliveira, Mucio T.; Soeiro, Alexandre; Nicolau, Jose C.; Ribeiro, Henrique B.; Chiang, Hsu P.; Sbano, João C.N.; Goldsweig, Andrew; et al.
Abstract : Background: It has recently been demonstrated that high-energy diagnostic transthoracic ultrasound and intravenous microbubbles dissolve thrombi (sonothrombolysis) and increase angiographic recanalization rates in patients with ST-segment–elevation myocardial infarction. We aimed to study the effect of sonothrombolysis on the myocardial dynamics and infarct size obtained by real-time myocardial perfusion echocardiography and their value in preventing left ventricular remodeling. Methods: One hundred patients with ST-segment–elevation myocardial infarction were randomized to therapy (50 patients treated with sonothrombolysis and percutaneous coronary intervention) or control (50 patients treated with percutaneous coronary intervention only). Left ventricular volumes, ejection fraction, risk area (before treatment), myocardial perfusion defect over time (infarct size), and global longitudinal strain were determined by quantitative real-time myocardial perfusion echocardiography and speckle tracking echocardiography imaging. Results: Risk area was similar in the control and therapy groups (19.2±10.1% versus 20.7±8.9%; P =0.56) before treatment. The therapy group presented a behavior significantly different than control group over time ( P <0.001). The perfusion defect was smaller in the therapy at 48 to 72 hours even in the subgroup of patients with no recanalization at first angiography (12.9±6.5% therapy versus 18.8±9.9% control; P =0.015). The left ventricular global longitudinal strain was higher in the therapy than control immediately after percutaneous coronary intervention (14.1±4.1% versus 12.0±3.3%; P =0.012), and this difference was maintained until 6 months (17.1±3.5% versus 13.6±3.6%; P <0.001). The only predictor of left ventricular remodeling was treatment with sonothrombolysis: the control group was more likely to exhibit left ventricular remodeling with an odds ratio of 2.79 ([95% CI, 0.13–6.86]; P =0.026). Conclusions: Sonothrombolysis reduces microvascular obstruction and improves myocardial dynamics in patients with ST-segment–elevation myocardial infarction and is an independent predictor of left ventricular remodeling over time.